2003
DOI: 10.1242/dev.00181
|View full text |Cite
|
Sign up to set email alerts
|

BMP signaling is required for septation of the outflow tract of the mammalian heart

Abstract: SUMMARY DEVELOPMENT AND DISEASE BMP signaling is required for septation of the outflow tract of the mammalian heart

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
137
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(144 citation statements)
references
References 61 publications
6
137
0
Order By: Relevance
“…This notion of distinct, dosage-dependent functions for Bmp signaling likely also applies to the SHF and SHF derivatives as suggested by the OFT phenotype of the Bmpr2 hypomorph previously reported by Lyons and colleagues (46). Moreover, we have recently found that Bmp2 and Bmp4 function cooperatively in the SHF to regulate distinct events in the forming OFT (L. Ma and J.F.M., unpublished observations).…”
Section: Wnt Signaling Is Critical For Development Of the Right Ventrsupporting
confidence: 70%
“…This notion of distinct, dosage-dependent functions for Bmp signaling likely also applies to the SHF and SHF derivatives as suggested by the OFT phenotype of the Bmpr2 hypomorph previously reported by Lyons and colleagues (46). Moreover, we have recently found that Bmp2 and Bmp4 function cooperatively in the SHF to regulate distinct events in the forming OFT (L. Ma and J.F.M., unpublished observations).…”
Section: Wnt Signaling Is Critical For Development Of the Right Ventrsupporting
confidence: 70%
“…A homozygous mouse defective for BMPR-II receptormediated signaling revealed outflow tract defects, including the absence of septation of the conotruncus below the valve level. 24 Further investigation of the BMP pathway in mouse cardiac development demonstrated that ablation of the BMP type I receptor ALK-3 in neural crest cells also leads to severe outflow tract defects, including failure of septation. 25 Taken together, these data raise the intriguing possibility that BMPR2 mutations may lead to congenital heart defects in humans and may be a predisposition to PAH.…”
Section: Discussionmentioning
confidence: 99%
“…BMP and FGF signaling pathways have previously been shown to be important for normal heart development including endocardial cushion formation, cushion elongation, and remodeling (Galvin et al, 2000;Gaussin et al, 2002;Delot et al, 2003;Jiao et al, 2003;Sugi et al, 2003Sugi et al, , 2004Somi et al, 2004;Ma et al, 2005;Lincoln et al, 2006a). A number of BMP ligands have been identified in the developing heart; in particular, BMP4 is expressed in the OFT myocardium adjacent to the endocardial cushions during early stages of valve development (Keyes et al, 2003).…”
Section: Discussionmentioning
confidence: 99%